(untitled) (Communications in Computational Physics, 2008)
We investigate the validity of stationary simulations for semiconductor quantum charge transport in a one-dimensional resonant tunneling diode via fluid type models. Careful numerical investigations to a quantum hydrodynamic model reveal that the transient simulations do not always converge to the steady states. In particular, growing oscillations are observed at relatively large applied voltage. A dynamical bifurcation is responsible for the stability interchange of the steady state. Transient and stationary computations are also performed for a unipolar quantum drift-diffusion model.